2003
DOI: 10.1007/s00415-003-1005-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in chronic obstructive pulmonary disease

Abstract: Some analogy exists between cognitive impairment in hypoxemic patients with chronic obstructive pulmonary disease (COPD) and Alzheimer's disease (AD). We purposed to verify whether the analogy extends to the cerebral perfusion pattern. Ten normal subjects, 15 COPD patients with and 18 without hypoxemia, and 15 patients with mild AD matched for age and educational level underwent brain perfusion single photon emission computed tomography (SPECT) and neuropsychological assessment. Normal subjects and non hypoxem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
4
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 33 publications
2
81
4
1
Order By: Relevance
“…Research on cognitive function assessed by single-photon-emission computed tomography in subjects with COPD indicated that worsening of hypoxemia may be associated with frontal-type cognitive decline. 31 However, current evidence would suggest that hypoxemia alone is not enough to account for the cognitive impairment in COPD. 14 Depressive symptoms in the subjects with bronchiectasis may be an important determinant for low cognitive ability in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Research on cognitive function assessed by single-photon-emission computed tomography in subjects with COPD indicated that worsening of hypoxemia may be associated with frontal-type cognitive decline. 31 However, current evidence would suggest that hypoxemia alone is not enough to account for the cognitive impairment in COPD. 14 Depressive symptoms in the subjects with bronchiectasis may be an important determinant for low cognitive ability in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proposed that intermittent and continuous hypoxia in COPD patients, which results from poor lung function, may lead to transient deficits in the metabolism of neurotransmitters in the central nervous system [29,30,31,32]. Other studies have suggested that in the late stage of the disease, as a consequence of decreased pulmonary function, cerebral blood perfusion is reduced, which may exacerbate ischemia in some brain regions and thus may increase subcortical atrophy [7,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that COPD patients exhibit earlier cognitive decline in age and health status than expected [5,6]. However, the mechanisms involved in the impairment of cognition and the relevant factors are complex and not fully understood [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of COPD was made according to the American Thoracic Society standards [12] . Only patients with PaO 2 ^56 mm Hg either at rest or at the end of the 6-min walking test while breathing room air were selected because cognitive impairment is highly prevalent in hypoxemic COPD patients [10,13] . Probable Alzheimer's disease or other conditions, such as cerebrovascular disease or hypothyroidism, and drugs apt to affect the cognitive status [14,15] were criteria of exclusion from the study.…”
Section: Methodsmentioning
confidence: 99%